The Role of Path-Goal Theory in Healthcare Leadership Improving Employee Motivation and Performance Outcomes - Anand , Dr.J.; Rajan , C.; Daniel , Dr.R. Moses; Chhabda , Dr. Parvindar Kaur; Sehgal , Dr. Rajesh (International Journal of Accounting and Economics Studies, 2025)
Effective leadership in health care is important to ensure high-level patient care, improve operational efficiency, and evaluate an induced task force. Path-laying theory provides a structured approach to lead through the alignment of the leader's needs and conditions in the workplace for better inspiration and an increase in performance. The paper checks the application of the path-target theory in the field of healthcare leadership and how the instructions, assistants, participants, and achievement-oriented leadership styles will affect employee engagement, job satisfaction, demographics, and overall performance. In this study, compared to a leadership approach, the effect was established on the workforce productivity, decision making, and patient care results. The findings led to the recommendations that the leadership styles, especially the path-target theory, should be dynamic and adapt their strategic approach according to the wide variety of health professionals when it comes to motivation and performance. Health care leaders are provided with practical recommendations to establish an atmosphere of cooperation and efficiency, to maximize the implementation of path-target theory. Future instructions for research are also proposed to pay attention to how the developed landscape of leadership will be within the adaptive healthcare settings.